The Implementation of International Baccalaureate (IB) Curriculum in Writing at Grade Eleven of SMA Singapore School Medan - Nani Manik; Arsen Pasaribu; Sondang Manik (Journal of English Language Teaching, Literatures, Applied Linguistic (JELTLAL), 2024)
The text emphasizes the significance of enhancing writing skills among EFL (English as a Foreign Language) students through active learning and meaningful engagement, advocating for a student-centered approach that fosters idea development through discussion and writing. It highlights the challenges faced by Grade 11 EFL students at Singapore School Medan, particularly regarding grammar mastery and practice opportunities, revealing that while 62% of students exhibit good writing skills, a notable portion struggles due to limited engagement and reluctance to communicate in English. The study suggests utilizing news media and guided practice to boost motivation and creativity, ultimately calling for more effective teaching strategies to improve writing outcomes. The sample of this study is 15 students. The researchers used purposive sampling to achieve the aim of the study. To collect the Semi-structured interview is a form of Interview. The finding of this research showed that in the pre-test, the students got a mean score of 43,75. In cycle 1, the mean score is 48,6.  In cycle 2, the mean score is 60,5 or categorized as moderate. In the post-test, the mean score is 75,8 categorized as good. Topic writing skills in EFL students by providing one learning topic makes students active in constructing meaning, text, dialogue, and experience, in expressing their ideas clearly at SMA Singapore School Medan